(untitled) - Chung, Kai Lai (River Edge, NJ, 2002)
Emphasizes the methodology of Brownian motion in the relatively simple case of one-dimensional space. Numerous exercises are included. For graduate students and researchers in probability and statistics. Softcover. Hardcover available.
Keywords: Brownian motion processes,Boundary value problems; Quá trình vận động Brown